(untitled) (Research, Society and Development, 2020)
The purpose of this article, was to report the experience of a change on a pedagogical proposal. The proposal considered the intention to overcome a traditional and centred curricular structure in a course with less integration, and, mostly, distant to the dietitians’ practice, driven by a collective effort with an emphasize in the main stages of the process. This change combined the theoretical assumption with the concept of higher education, as an element of training to graduate a health professional. This considered the interprofessional and disciplinary laws and regulations and the national curriculum as a legal and conceptual framework. The process was identified by collective and listening actions, including, course perceptions of first-year students, experiences and skills from dietitians, and profiles of senior-year students. Workshops with lecturers and students were done to analyze the course syllabus. Findings have shown that the pedagogical foundations comprehension of the architecture curriculum, allowed the development of an accessible environment with succeeding approaches between the proposal and reality. Finally, the qualification of all individuals involved, with institutional support, facilitate changes on learning practices as has been requested during COVID-19 period.